Analysis of the Impact of Charging When Used on Laptop Battery Performance and Stability - Amiruddin, Syuraih; Arifin, Sulthon Muakhor; Saragih, Yuliarman (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
In the current era, laptops have become important electronic devices in various activities. However, excessive use and the habit of charging while using it can affect the performance and stability of the laptop battery. This research uses a qualitative descriptive approach with interview methods and literature studies to analyze the impact of charging during use on battery performance and stability. The results of interviews with technicians show that battery damage often occurs due to overcharging or heavy use when charging. Factors such as Cycle Count Limit, State of Charge, Depth of Discharge, temperature, and voltage also affect battery performance. Preventing battery damage can be done by managing battery charging wisely, avoiding excessive temperatures, using a charger according to specifications, and removing the battery during heavy use. With this understanding, it is hoped that users can extend the service life and maintain laptop battery performance more effectively.